Endoscopic transpapillary drainage for walled-off pancreatic necrosis with complete main pancreatic duct disruption by metallic stent placement: A retrospective study - Meng, Yajie; Ding, Jiewen; Tian, Chuan; Wang, Min; Tang, Kejiang (Frontiers in Medicine, 2022)
Background Walled-off pancreatic necrosis (WOPN) is a serious complication of acute necrotizing pancreatitis (ANP) and may lead to disruption of the main pancreatic duct (MPD). Endoscopic passive transpapillary drainage (PTD) is an effective method for treating MPD disruptions. However, WOPN with complete MPD disruption is usually accompanied by disconnected pancreatic duct syndrome (DPDS), especially with infected necrosis. Endoscopic PTD with a fully covered self-expanding metallic stent (FCSEMS) and a plastic stent placement may have the potential for future application in treating complete MPD disruption in patients with WOPN. Methods Patients with WOPN caused by ANP were classified according to the 2012 Atlanta classification and definition. In all patients, ERCP was performed 2 times. First, 3 patients were diagnosed with complete MPD disruption by ERCP. At the time of diagnosis, a plastic pancreatic stent (7Fr) was placed. Second, they underwent endoscopic PTD for WOPN with complete MPD disruption in which an FCSEMS and plastic stent placement were the only access routes to the necrotic cavity. Results The etiology of pancreatitis in these patients was of biliary, lipogenic, and alcoholic origin. The WOPN lesion size ranged from 6.5 to 10.2 cm in this study, and the type of WOPN was mixed in two cases and central in one case. The type of MPD disruption was complete in all three patients. The locations of disruption included the pancreatic body and head. The time from occurrence to the first ERCP was 18, 23, and 26 days, respectively. The main symptoms were abdominal pain, abdominal distention, fever, gastrointestinal obstruction, and/or weight loss. The three patients with symptomatic WOPN and MPD disruption underwent endoscopic PTD with FCSEMS and plastic pancreatic stent placement. Technical and therapeutic successes were achieved in 3/3 of patients. The mean time of stenting was 28–93 days. The clinical symptoms connected with WOPN and collection disappeared postoperatively in all three patients. During the follow-up period of 4–18 months, no patient developed collection recurrence or other complications, such as gastrointestinal bleeding or reinfection. All patients recovered uneventfully. Conclusion In patients with WOPN with complete MPD disruption, endoscopic PTD with FCSEMSs and plastic stent placement may be an effective and safe method of treatment.